Structure and photoluminescence properties of red-emitting apatite-type phosphor NaY9(SiO4)6O2:Sm3+ with excellent quantum efficiency and thermal stability for solid-state lighting. Issue 1 (December 2017) - Mei, Lefu; Liu, Haikun; Liao, Libing; Zhang, Yuanyuan; Kumar, R.
Abstract A novel red-emitting phosphor NaY9 (SiO4 )6 O2 :Sm3+ (NYS:Sm3+ ) was synthesized and the X-ray diffraction and high-resolution TEM testified that the NYS compound belongs to the apatite structure which crystallized in a hexagonal unit cell with space group P63 /m. The novel phosphor boasts of such three advantageous properties as perfect compatible match with the commercial UV chips, 73.2% quantum efficiency and 90.9% thermal stability at 150 °C. Details are as follows. NYS:Sm3+ phosphor showed obvious absorption in the UV regions centered at 407 nm, which can be perfectly compatible with the commercial UV chips. The property investigations showed that NYS:Sm3+ phosphor emitted reddish emission with CIE coordination of (0.563, 0.417). The optimum quenching concentration of Sm3+ in NYS phosphor was about 10%mol, and the corresponding concentration quenching mechanism was verified to be the electric dipole–dipole interaction. Upon excitation at 407 nm, the composition-optimized NYS:0.10Sm3+ exhibited a high quantum efficiency of 73.2%, and its luminescence intensity at 150 °C decreased simply to 90.9% of the initial value at room temperature. All of the results indicated that NYS:Sm3+ is a promising candidate as a reddish-emitting UV convertible phosphor for application in white light emitting diodes (w-LEDs).